(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Municipal solid waste compost is an organic soil additive that can be used in agricultural production, improving soil physical properties, increasing both water retention and supply of essential nutrients. In this study three different types compost were studied. One produce by Lahore City Government second from Patoki compost and third from PCSIR Labs Lahore. These were analyzed for pH, conductivity, organic matter, total nitrogen, P2O5 and K2O by using AOAC method. Average moisture, pH, carbon were highest in Patoki compost while organic matter was lowest (27%) in Paktoki and highest (56%) in PCSIR sample. Potassium was maximum in Lahore City Government and Patoki compost, minimum in PCSIR samples. The C/N ratio in all compost samples suggest that compost were stable and mature. The concentrations of Pb and Zn were also studied. Key words: Compost, Organic matter, Carbon nitrogen ratio, Nutrients. DOI = 10.3329/bjsir.v43i3.1145 Bangladesh J. Sci. Ind. Res. 43(3), 301-308, 2008